Efecto de fecha y tipo de poda en frambuesa roja "Malling autumn Bliá" - Parra Quezada, R.A.=700 1 Guerrero Prieto, V.M.; Arreola Avila, J.G.
(En, Es)
Ilus., 16 ref.
Keywords: RUBUS IDAEUS; PODA; FLORACION; PRODUCCION; CALIDAD; FRUTO; MEXICO; FRAMBUESA ROJA